Violência no espaço escolar e a necessidade da cultura de paz: um estudo a partir da realidade do 9º ano de uma escola estadual em Luziânia - Purificação, Marcelo Máximo (2014)
This research has as its central focus the violence at school. The overall objective was to analyze, from the viewpoint of students in the 9th grade of elementary education in a state school in Luziania, Goiás, the relationships established in the school environment among students and between teachers and students, which factors provide mapping conflicts in interpersonal relationships. The methodological approach was qualitative, using mainly tools for systematic observation, document analysis, questionnaires and semi-structured interviews nature, with the purpose of collecting data from the students, teachers and other professionals in the technical and administrative staff of the school. Data analysis used theoretical contribution as authors like Arendt (1994), Bourdieu (2001), Abramovay (1999), Charlot (1999), among others. Constant dialogue between the data found in the search field and the ideas of scholars have allowed the knowledge and understanding of violence at schools. The main results show that school violence among students promotes the disinterest in studies and insecurity among teachers and loss of motivation at work and fear. The actors do not perceive the school as an environment for conflict mediation. It shows it as a proposal for the establishment of citizen school teacher training and the development of a culture of peace that the social work and human values, ethics, solidarity, respect for human rights. So it was back to critical reflection for the conception of man as the main protagonist of these behaviors of violence, peace, love and understanding. To substantiate the above concepts we used in this work, several theorists, however, had as guiding René Girard and Pierre Bourdieu. The desire and violence are fundamental features of giardiano thought, because desire, according to the author is the object that motivates the conflict and this gives rise to the development of violence. Have Bourdieu, was important in order to guide the dialogue and to understand the school as a promoter area of symbolic violence. It follows, that the Holy One, may be studied and discussed in other environments outside of religions, such as the school, and their representativeness, subjectively speaking, can help the reflection that both peace and violence are processes built from the relations between beings (un) human and can then be taught and / or learned. In this sense, it is critical (re) think the actions that should be built into the daily school units.